Stabilization, Safety, and Security of Distributed Systems 17th International Symposium, SSS 2015, Edmonton, AB, Canada, August 18-21, 2015, Proceedings - Pelc, Andrzej; Schwarzmann, Alexander A. (Theoretical Computer Science and General Issues, 2015)
This book constitutes the refereed proceedings of the 17 International Symposium on Stabilization, Safety, and Security of Distributed Systems, SSS 2015, held in Edmonton, AB, Canada, in August 2015. The 16 regular papers presented together with 8 brief announcements and 3 keynote lectures were carefully reviewed and selected from 38 submissions. The Symposium is organized in several tracks, reflecting topics to self-*properties. The tracks are self-stabilization; fault-tolerance and dependability; ad-hoc and sensor networks; mobile agents; system security in distributed computing; and formal methods and distributed algorithms.